Donor/recipient origin of lung cancer after lung transplantation by DNA short tandem repeat analysis - De Wolf, Julien; Robin, Edouard; Vallee, Alexandre; Cohen, Justine; Hamid, Abdul; Roux, Antoine; Leguen, Morgan; Beaurepere, Romane; Bieche, Ivan; Masliah-Planchon, Julien; Glorion, Matthieu; Allory, Yves; et al. (Frontiers in Oncology, 2023)
Background Lung cancer is more common in posttransplant recipients than in the general population. The objective of this study was to examine the chimerism donor/recipient cell origin of graft cancer in recipients of lung transplant. Methods A retrospective chart review was conducted at Foch Hospital for all lung transplantations from 1989 to 2020. Short tandem repeat PCR (STR-PCR) analysis, the gold standard technique for chimerism quantification, was used to determine the donor/recipient cell origin of lung cancers in transplant patients. Results Fourteen (1.4%) of the 1,026 patients were found to have graft lung cancer after lung transplantation, and one developed two different lung tumors in the same lobe. Among the 15 lung tumors, 10 (67%) presented with adenocarcinoma, four (27%) with squamous cell carcinoma and one with small cell lung cancer. STR analysis showed that the origin of the cancer was the donor in 10 patients (71%), the recipient in three patients (21%), and was undetermined in one patient. Median time to diagnosis was 62 months. Conclusion The prevalence of lung cancer in lung transplant recipients is very low. However, the results of our study showed heterogeneity of genetic alterations, with 21% being of recipient origin. Our results highlight the importance of donor selection and medical supervision after lung transplantation.